AN INVESTIGATION OF GRADUATE STUDENTS USAGE OF SYNCHRONOUS LEARNING PLATFORMS IN THE POST COVID-19 ERA - Rita Pusvitasari; Chantana Viriyavejakul; Piyapong Sumettikoon (My University, 2023)
Alternative methods for instruction after a pandemic for higher education applied synchronous learning platforms. Graduate students could take classes from any area employing their mobile devices and internet connectivity. The study was to expand technology satisfaction and DeLone and McLean’s model among graduate students employing synchronous learning platforms post COVID-19. Data obtained from a survey and 204 participants of Thai and international students filled the questionnaires. The proposed hypotheses analyzed applying a type of Partial Least Squares. The results denoted that computer self-efficacy, service, information, and system quality significantly and directly influences TAM (perceived usefulness and perceived ease of use). In addition, satisfaction was effected by TAM. System quality has higher important in increase satisfaction of synchronous learning platforms in the post COVID-19. The findings will assist universities and stakeholders in service planning use synchronous learning platforms in remote learning. Managerial implications can be discussed. Keywords: Synchronous Learning Platforms, DeLone and McLean Model, Technology Satisfaction Model, Post COVID-19 Era DOI： https://doi.org/10.35741/issn.0258-2724.58.2.3
Keywords: E-Learning; Graduate students; Technology Acceptance Model; Organizational and Employee Performance